Improvement of Measurement Efficiency in Multistage Tests by Targeted Assignment - Berger, Stéphanie; Verschoor, Angela J.; Eggen, Theo J. H. M.; Moser, Urs (Frontiers in Education, 2019)
A good match between item difficulty and student ability ensures efficient measurement and prevents students from becoming discouraged or bored by test items that are too easy or too difficult. Targeted test designs consider ability-related background variables to assign students to matching test forms. However, these designs do not consider that students might significantly differ in ability within the resulting groups. In contrast, multistage test designs consider students’ performance during test taking to route them to the most informative modules. Yet, multistage test designs usually include one starting module of moderate difficulty in the first stage, which does not account for differences in ability. In this paper, we investigated whether measurement efficiency can be improved by targeted multistage test designs that consider ability-related background information for a targeted assignment at the beginning of the test and performance during test taking for selecting matching test modules. By means of simulations, we compared the efficiency of the traditional targeted test design, the multistage test (MST) design, and the targeted multistage test (TMST) design for estimating student ability. Furthermore, we analyzed the extent to which the efficiency of the different designs depends on the correlation between the ability-related background variable and the true ability, students’ ability level and their categorization into an ability group, and the length of the starting module. The results indicated that TMST designs were generally more efficient for estimating student ability than targeted test designs and MST designs, especially if the ability-related background variable correlated high with and, thus, was a good indicator of, students’ true ability. Furthermore, TMST designs were particularly efficient in estimating abilities for low- and high-ability students within a given population. Finally, very long starting modules resulted in less efficient estimation of low and high abilities than shorter starting modules. However, this finding was more prominent for MST than for TMST designs. In conclusion, TMST designs are recommended for assessing students from a wide ability distribution if a reliable ability-related background variable is available.